2010
DOI: 10.1016/j.fitote.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids with prolyl oligopeptidase inhibitory activity isolated from Scutellaria racemosa Pers

Abstract: Prolyl oligopeptidase (POP) is a serine protease highly expressed in the brain that hydrolyses peptide bonds at the carboxyl terminal of prolyl residues. There is evidence that this enzyme participates in several functions of the central nervous system. Scutellaria racemosa Pers demonstrated significant and selective POP inhibition. Fractionation of the hydroalcoholic extract resulted in the isolation of four main constituents identified for the first time from S. racemosa Pers, the triterpenoid lupeol (1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 30 publications
1
22
0
2
Order By: Relevance
“…Hispidulin and other phytochemical were isolated from the leaves of C. chinense 58 . Fractionation of hydroalcoholic extract of S. racemosa Pers resulted in the isolation of four main constituents including hispidulin 59 . Phytochemical study of leaves of Leuzea carthamoides was performed and the result showed the presence of seven natural compounds including hispidulin 60 .…”
Section: Analytical Aspects Of Hispidulinmentioning
confidence: 99%
“…Hispidulin and other phytochemical were isolated from the leaves of C. chinense 58 . Fractionation of hydroalcoholic extract of S. racemosa Pers resulted in the isolation of four main constituents including hispidulin 59 . Phytochemical study of leaves of Leuzea carthamoides was performed and the result showed the presence of seven natural compounds including hispidulin 60 .…”
Section: Analytical Aspects Of Hispidulinmentioning
confidence: 99%
“…The residue was purified by silica gel chromatography (EtOAc−n-hexane, 1:1) to give hispidulin (89 mg, 80%) as a yellow microcrystalline powder; mp 275−277°C (lit. 32 Expression and Purification of Pim-1. The production and purification of the recombinant His 6 -tagged Pim-1 for crystallography have been described previously.…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…Some natural products are known POP inhibitors in the micromolar range such as the flavonoids baicalin [7] and oroxylin [8], the alkaloid berberine [9], and 6-(8´Z-pentadecenyl)salicylic acid [10].…”
Section: Introductionmentioning
confidence: 99%